Empowerment of Oil Palm Plantation Farmer Groups through PENA (Pestisida Nabati) Socialization - Sutikno, Agus; Putri, Vivin Jenika; Zamaya, Yelly; Pramana, Angga; Rahmah, Anania; AR, Nur Hasnah; Ruzain, Raihanatu Binqalbi (Universitas Lancang Kuning, 2024)
To increase crop yields, farmers use various pesticides to prevent pest attacks. Currently, the use of chemical pesticides by farmers in agriculture and horticulture is increasing, and is a concern for environmental sustainability. The purpose of this service activity is to increase farmers' knowledge about the production and use of vegetable pesticides or pesticides made from natural ingredients. This activity was carried out in Riau Province, Buatan Baru Village, Kerinci Kanan District, Siak Regency. The output of this service is the increased understanding and knowledge of the community about the benefits of the production and use of Pestisida Nabati (PENA) and their impact on the environment.